Data-driven state of charge estimation of lithium-ion batteries: Algorithms, implementation factors, limitations and future trends - Hossain Lipu M.S.; Hannan M.A.; Hussain A.; Ayob A.; Saad M.H.M.; Karim T.F.; How D.N.T. (Elsevier Ltd, 2023)
Automotive batteries; Charging (batteries); Digital storage; Electric automobiles; Fossil fuels; Fuel storage; Ions; Lithium-ion batteries; Battery storage system; Data-driven algorithm; Detailed classification; Evaluation indicators; Global carbon emission; High energy densities; State-of-charge estimation; Vehicle applications; Battery management systems